EKSTRAKSI ZAT WARNA ALAMI CAMPURAN BIJI PINANG, DAUN SIRIH, GAMBIR DAN PENGARUH PENAMBAHAN KMnO4 TERHADAP PEWARNAAN KAYU JENIS ALBASIA - Bogoriani, N. W. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
The research about extraction of natural dies from the mixtures of areca nut, betel leaf, gambier, and the effect of addition of KMnO4 towards surface coloration of albasia wood (Paraserianthes falcataria) was carried out. The extraction of mixture of natural dye was conducted by heating in water for two hours. 10,00 gram of each samples of betel leaf, areca nut, and gambier were refluxed and resulted in 28,60%, 40,10%, and 30,20% respectively. According to fitochemical test, the betel leaf extract contain flavonoid, tannin, and carotenoid, whereas the areca nut and gambier extracts contain flavonoid and tannin. The optimum mass ratio and mass of KMnO4 for coloration were resulted in optimum mass 10:10:5 and 0,25 gram respectively. This showed that the addition of KMnO4 strengthen the bond between dye and wood fiber and sharpen the resulted color. This was proven by color endurance test by soaking the object in 1% of detergent water for 15 minutes. The dye without KMnO4 was easy to fade out, whereas the dye with KMnO4 was more resistant. The resulted color varies from reddish brown, brown, to deep brown.
Keywords: areca nut, betel leaf, gambier, reflux, KMnO4